2015
DOI: 10.1037/mgr0000025
|View full text |Cite
|
Sign up to set email alerts
|

Using undergraduate grade point average as a selection tool: A synthesis of the literature.

Abstract: As educational attainment becomes increasingly more important in employment settings, undergraduate grade point average (GPA) will persist in being an attractive selection tool. It is important that recruitment professionals understand the implications of the use of this measure. Thus, this article aims to unify the GPA literature in order to offer guidelines for practice based on current research. Common themes within the literature are reviewed to address topics such as what GPA reflects as well as the relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 34 publications
(71 reference statements)
1
34
0
5
Order By: Relevance
“…This outcome is paramount, as the relationship between higher grades at university are positively related to future employability of graduates, as it has been widely evidenced by previous research (Baird, 1985, Baker, 2008Brown, 1984;Gokuladas, 2011;Hassanbeigi et al, 2011;Imose and Barber, 2015;Johansen, 2014;Schick and Kunnecke, 1982;Thoms et al, 1999).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This outcome is paramount, as the relationship between higher grades at university are positively related to future employability of graduates, as it has been widely evidenced by previous research (Baird, 1985, Baker, 2008Brown, 1984;Gokuladas, 2011;Hassanbeigi et al, 2011;Imose and Barber, 2015;Johansen, 2014;Schick and Kunnecke, 1982;Thoms et al, 1999).…”
Section: Discussionmentioning
confidence: 87%
“…In the first place, earlier research found strong connections between higher academic performance and heightened employability (Baird, 1985, Baker, 2008Campion and Brown, 1984;Gokuladas, 2011;Hassanbeigi et al, 2011;Imose and Barber, 2015;Johansen, 2014;Schick and Kunnecke, 1982;Thoms et al, 1999). Consequently the first hypothesis is weather there were any differences on the academic achievement among students of the ARA Groups and regular students:…”
Section: Research Hypothesismentioning
confidence: 96%
See 3 more Smart Citations